A Case on Kingfisher-Air Deccan Merger: The Marriage of Convenience - Goyal, Subrabhi; Ray, Prantik (Indian Journal of Marketing, 2012)
This case study is a sequel of the case titled, ’The First Low Cost Carrier of India’ written by the present author in the year 2006, when the homegrown airline Air Deccan was at its zenith and was becoming a game changer of the Aviation sector in India. Started in 2003, Air Deccan brought a revolution in air travel, making air travel in India an affordable proposition for the common man. However, in 2007, the airline nose dived and Captain Gopinath, its CEO, had to succumb to the consolidation proposed by Dr. Vijay Mallya of the Kingfisher Airline group. This study is, therefore, an attempt to elucidate the strategic moves made by the acquirer - Vijay Mallya to restructure and reposition the erstwhile Air Deccan into a new combined entity - Kingfisher Red. Furthermore, as the merger story unfolds, it brings out the truism of consolidation - that one man’s gain is another man’s loss.